Early protein C activation is reflective of burn injury severity and plays a critical role in inflammatory burden and patient outcomes. Issue 1 (February 2022) - Zhao, Ruilong; Lang, Thomas Charles; Kim, Albert; Wijewardena, Aruna; Vandervord, John; McGrath, Rachel; Fulcher, Gregory; Xue, Meilang; Jackson, Christopher
Graphical abstract: Highlights: Activated protein C increases from a nadir on Day 3 following a severe burn injury. More severe burns trigger greater protein C activation and a functional depletion. Loss of this cytoprotective agent leads to elevated inflammation and worse outcomes. The protein C system provides ideal burns biomarkers with therapeutic potential. Abstract: Background: Navigating the complexities of a severe burn injury is a challenging endeavour where the natural course of some patients can be difficult to predict. Straddling both the coagulation and inflammatory cascades that feature strongly in the burns systemic pathophysiology, we propose the pleiotropic protein C (PC) system may produce a viable biomarker to assist traditional evaluation methods for diagnostic and prognostic purposes. Methods: We enrolled 86 patients in a prospective observational cohort study. Over three weeks, serial blood samples were taken and measured for PC, activated (A)PC, their receptor endothelial protein C receptor (EPCR), and a panel of inflammatory cytokines including C-reactive protein (CRP), tumour necrosis factor-α, interleukin (IL)-1β, IL-6, IL-8, and IL-17. Their temporal trends were analysed alongside clinical factors including burn size, burn depth, presence of inhalational injury, and a composite outcome of requiring increased support. Results: (i) APC increased from a nadir on Day 3 (2.3 ± 2.1 ng/mL vs 4.1 ± 2.5 ng/mL by Day 18, p  < 0.0005), only becoming appropriately correlated to PC from Day 6 onwards ( r  = 0.412–0.721, p  < 0.05 for all Days 6–21). (ii) This early disturbance in the PC system was amplified in the more severe burns (≥30% total body surface area, predominantly full thickness, or with inhalational injury), which were characterised by a marked fall in PC activation (approximated by APC/PC ratio) and APC levels during Days 0–3 with low unchanged PC levels. Critically low levels of this cytoprotective agent was associated with greater inflammatory burden, as reflected by significantly elevated CRP, IL-6, and IL-8 levels in the more severe compared to less severe burns, and by negative correlations between both PC and APC with most inflammatory cytokines. (iii) Alongside clinical markers of severity at admission (burn size, burn depth, and presence of inhalational injury), only Day 0 APC/PC ratio (OR 1.048 (1.014–1.083), p  = 0.006), APC (OR 1.364 (1.032–1.803), p  = 0.029), PC (OR 0.899 (0.849–0.953), p  < 0.0005), and not any inflammatory cytokines were predictive markers of requiring increased support. Uniquely, decreased Day 0 PC was further individually associated with each increased total length of stay, ICU length of stay, intravenous fluid resuscitation, and total surgeries, as well as possibly mortality. Conclusion: An early functional depletion of the cytoprotective PC system provides a physiological link between severe burns and the cytokine storm, likely contributing to worse outcomes. Our findings on the changes in APC, PC and PC activation during this pathological state support APC and PC as early diagnostic and prognostic biomarkers, and provides a basis for their therapeutic potential in severe burn injuries.